Conflicts of Law and Morality. - Greenawalt, Kent (Clarendon law series., 1989)
Powerful emotion and pursuit of self-interest have many times led people to break the law with the belief that they are doing so with sound moral reasons. This study is a comprehensive philosophical and legal analysis of the gray area in which the foundations of law and morality clash. In examining the extent of the obligations owed by citizens to their government, Greenawalt concentrates on the possible existence of a single source of obligation that reaches all citizens and all laws.